Glued-laminated (glulam) beams is one of engineered wood products used for structural applications. The objective of this research is to evaluate characteristics of glulam beams made from Acacia mangium Willd. Laminations used were 2, 4, 6, 8 and 12 cm in widthnesses, 2 cm in thickness and 260 cm in length. Each lamination was graded using Machine Stress Grading (namely by Panter or plank sorter) to determine the modulus of elasticity (MOE) value. The glulam beams was 6 cm x 12 cm in five - Evalina HERAWATI; Muh. YUSRAM MASSIJAYA; Naresworo NUGROHO (Departemen Hasil Hutan, IPB, 2008)
Glued-laminated (glulam) beams is one of engineered wood products used for structural applications. The objective of this research is to evaluate characteristics of glulam beams made from Acacia mangium Willd. Laminations used were 2, 4, 6, 8 and 12 cm in widthnesses, 2 cm in thickness and 260 cm in length. Each lamination was graded using Machine Stress Grading (namely by Panter or plank sorter) to determine the modulus of elasticity (MOE) value. The glulam beams was 6 cm x 12 cm in five types of cross-section which arranged by various widths and those MOE of laminations. Glulam beams were bonded by water based polymer isocyanate (WBPI) using 280 g/m2 double glue spread. The research results showed that glulam beams made from A. mangium Willd. fulfilled the JAS 234:2003 standard as on following properties: moisture content, MOE, MOR, shear strength and immersion delamination test. However, performance of glulam was unsatisfactory in wood failure ratio and boiling water soak delamination test. Keywords: Glulam beam, MOE, MOR, shear strength, delamination